Baseball state by state : major and Negro league players, ballparks, museums and historical sites - Jensen, Chris, 1963- (McFarland & Co., 2012)
"From Alabama to Wyoming, this book provides information every fan should know about the fifty U.S. states. Each chapter covers the baseball history of of a state, its must-see sites (including museums and ballparks), career leaders in nine statistical categories, nicknames, and a roster of the all-time best native-born major and Negro League players"--Provided by publisher